Impact of the ClassMaker App on the Performance of Undergraduates in Online Learning of ICT: The University of Ilorin Experience - Onasanya, Temitayo Omolara; Attah, Justina Ojoma; Otemuyiwa, Bridget Idowu; Onasanya, Samuel Adenubi (West African Journal of Open and Flexible Learning, 2021)
Assessment and evaluation in the educational process have a profound and well-established link to student performance. This paper determines the impact of the ClassMarker app on the performance of undergraduates in online learning of ICT in the University of Ilorin. The study adopted a true experimental design of post-test only design. The population of the study consisted of all 300 level undergraduates of Educational Technology Department, University of Ilorin. The sample of the study was randomly selected 30 students, 300 level undergraduates of the Educational Technology Department, University of Ilorin. 15 students in the controlled group and 15 in the experimental group. Data collected were analysed using mean and standard deviation to answer the research question that guided the study. The three hypotheses raised were tested using independent samples t-test at 0.05level of significance. Findings revealed that undergraduates' in the experimental group performed better than their counterpart in the controlled group. Also, gender has so significant difference in the performance of undergraduates' in online learning of ICT. It was recommended among others that lecturers in the online learning environment should be encouraged to use the ClassMarker as a tool for assessment because it has a significant impact on the performance of the students. Abstrait L'appréciation et l'évaluation dans le processus éducatif ont un lien profond et bien établi avec la performance des étudiants. Cet article détermine l'impact de l'application ClassMarker sur la performance des étudiants de premier cycle dans l'apprentissage en ligne des ITC à University of Ilorin. L'étude a adopté une véritable conception expérimentale de conception post-test uniquement. La population de l'étude était composée des 300 étudiants de premier cycle du département de Technologie Educative de University of Ilorin. L'échantillon de l'étude a été sélectionné au hasard 30 étudiants de 3e année au niveau de la licence du Département de Technologie Educative, University of Ilorin. 15 étudiants au groupe de contrôle et 15 au groupe expérimental. Les données recueillies ont été analysées en utilisant la moyenne et l'écart-type pour répondre à la question de recherche qui a guidé l'étude. Les trois hypothèses soulevées ont été testées à l'aide d'un test t d'échantillons indépendants à un niveau de signification de 0,05. Les résultats ont révélé que les étudiants de premier cycle du groupe expérimental avaient de meilleurs résultats que leurs homologues du groupe de contrôle. En outre, le genre a une différence si significative dans la performance des étudiants de premier cycle dans l'apprentissage en ligne des ICT. Il a été recommandé, entre autres, que les enseignants de l'environnement d'apprentissage en ligne soient encouragés à utiliser le ClassMarker comme outil d'évaluation, car il a un impact significatif sur les performances des étudiants.